A Review of Current Noninvasive Imaging Surveillance Practices for Deep Venous Arterialization Procedures. Issue 2 (June 2021) - Yan, Qi; Treffalls, John A.; Ferrer, Lucas; Davies, Mark G.
Venous arterialization is an increasingly common procedure performed in patients with critical limb-threatening ischemia (CLTI) where there are no open or percutaneous revascularization options. This study aims to review the imaging follow-up for venous arterialization described in the literature. A systematic review was performed on venous arterialization studies for CLTI using the PRISMA methodology. A literature search was performed on 5 databases from inception. We included all original studies, case reports, and reviews regarding venous arterialization for all pathologies. We excluded free standing abstracts, animal studies, other than lower extremity, and foreign language studies. Our search strategy yielded 23 studies that met inclusion criteria, with 16 studies reporting a specific value from at least one surveillance imaging methodology. Most studies used Duplex imaging (16 studies) and TCPo2 (9 studies). Only 9 studies provided any detail regarding the Duplex findings. One study used focal peak systolic velocity (PSV) gradient (PSV at the lesion in the graft divided by PSV in a proximal segment of the graft) above 2.5 as an indicator for flow-inhibiting venous valves or stenosis in the graft. Another study reported a turbulent flow pattern in the graft, elevating peak velocities to 100 to 200 cm/s throughout the bypass. Four studies reported flow volume measurement through the bypass or in pedal vein ranging from 40 to 437 mL/min. Seven studies reported a mean increase of 18.7 mmHg in TCPo2 . Eighty-two percent of patients saw an improvement of TCPo2 in 2 studies. To date, no criteria have been identified that are predictive of the success or failure of deep vein arterialization. Venous arterialization is an increasingly common procedure in the "no-option" diabetic patient. Duplex imaging with TCPo2 offers the most appropriate means of surveillance; however, the literature is sparse with no guidance on normal or critical values.